Cyclophosphamide Exposure Causes Long-Term Detrimental Effect of Oocytes Developmental Competence Through Affecting the Epigenetic Modification and Maternal Factors’ Transcription During Oocyte Growth - Yang, Weijie; Ma, Yerong; Jin, Jiamin; Ren, Peipei; Zhou, Hanjing; Xu, Shiqian; Zhang, Yingyi; Hu, Zhanhong; Rong, Yan; Dai, Yongdong; Zhang, Yinli; Zhang, Songying (Frontiers in Cell and Developmental Biology, 2021)
Cyclophosphamide (CTX) is widely used in various cancer therapies and in immunosuppression, and patients can still have babies after CTX chemotherapy. CTX directly causes primordial follicle loss with overactivation and DNA damage-induced apoptosis.Previous studies have shown that maternal exposure to CTX before conception increases the incidence of birth abnormalities and alters the methylation of genes in the oocytes of offspring.Mice were treated with a single dose of CTX (100 mg/kg) at post-natal day 21 and sacrificed 47 days later when primordial follicles surviving chemotherapy developed to the antral stage.Acute DNA damage and acceleration of the activation of primordial follicles after CTX treatment were repaired within several days, but the remaining follicle numbers remarkably decrease. Although partial surviving primordial follicle were developed to mature oocyte, oocyte quality haemostasis was impaired exhibiting aberrant meiosis progression, abnormal spindle and aneuploidy, mitochondrial dysfunction and increased endoplasmic reticulum stress. Thereafter, embryo development competency significantly decreased with fewer blastocyst formation after CTX exposure. CTX treatment resulted in alteration of DNA methylations and histone modifications in fully-grown GV oocytes. Single-cell RNA-seq revealed CTX treatment supressed multiple maternal genes’ transcription including many methyltransferases and maternal factor YAP1, which probably accounts for low quality of CTX-repaired oocyte. In vitro addition of lysophosphatidic acid (LPA) to embryo culture media to promote YAP1 nuclear localization improved CTX-repaired embryo developmental competence. This study provides evidence for the consistent toxic effect of CTX exposure during follicle development, and provide a new mechanism and new insights into future clinical interventions for fertility preservation.